An intragenic methylated region in the imprinted Igf2 gene augments transcription - Murrell, Adele (Oxford University Press, 2001)
DNA methylation is usually associated with transcriptional silencing, but in the imprinted mouse Igf2 gene, the paternally expressed copy is methylated in two discrete differentially methylated regions (DMRs). DMR1 is located upstream of the fetal promoters and has been shown to be a methylation sensitive silencer. Here we examine the role of the intragenic DMR2 by gene targeting. In contrast to DMR1, deletion of DMR2 on the maternal allele did not lead to activation of the silent Igf2 gene. Deletion of a 54 bp methylated core region in DMR2 on the paternal allele, however, reduced Igf2 mRNA levels and was associated with fetal growth retardation. Nuclear run-on assays showed that the core region influenced transcription initiation, and luciferase reporter assays suggested that its methylation increases transcription. These results reveal a novel mechanism of gene expression whereby intragenic methylation can increase levels of transcription.